PENGARUH PENAMBAHAN SERBUK KAYU SEBAGAI SUBSTITUSI AGREGAT HALUS DAN BESTMITTEL SEBAGAI ZAT ADITIF TERHADAP KUAT TEKAN BETON - M. Sazili Harnawansyah; Bambang Hidayat Fuady1; Sucita Maharany; Titi Sandora (Politeknik Negeri Sriwijaya, 2023)
ABSTRAC The more advanced and rapid development in Indonesia, especially in the field of concrete construction, therefore concrete is required to be more innovative in order to produce more economical and high quality concrete and a faster hardening process in order to save time in the work of a building. This study uses added material in the form of teak wood powder as a substitute for fine aggregate as much as 0%, 2.5%, 5%, 7.5% and bestmittel additives as much as 0.5%. The addition of sawdust was carried out to determine its effect on the compressive strength of concrete, this study also added bestmittel additives to accelerate hardening of the concrete and increase the quality of the compressive strength of concrete. In this study, the concrete was made in the form of a cylinder with a size of 15 cm x 30 cm with a total of 36 specimens, the test was carried out within 7 days, 14 days, and 28 days with a concrete quality of fc' 25 MPa based on SNI 03-2834- 2000. The test results showed that the compressive strength of concrete at 0% sawdust was 26.124 MPa, 2.5% sawdust and bestmittel 0.5% was 27.067 MPa, 5% sawdust and 0.5% bestmittel was 22.541 MPa, 7 sawdust. 5% and bestmittel 0.5% of 20.56 MPa. This shows that the addition of sawdust as a substitute for fine aggregate and bestmittel additives increases the compressive strength of concrete by 3.609% at the percentage of 2.5% sawdust and 0.5% bestmittel additives, while the addition of 5% and 7.5 percentages of sawdust. % with 0.5% bestmittel additives tend to experience a decrease in the compressive strength of concrete. Keywords : Concrete, sawdust, bestmittel, compressive strength